1998
DOI: 10.1046/j.1440-169x.1998.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and in situ hybridization analysis of estrogen receptor in the developing gonad of the red‐eared slider turtle, a species with temperature‐dependent sex determination

Abstract: Many reptiles exhibit temperature-dependent sex determination where the incubation temperature of the egg determines the gonadal sex of the individual. If exogenous estrogen is administered during the temperature-sensitive period to embryos incubating at a male-producing temperature, the temperature effects can be overridden and females will be produced. Inhibiting production of endogenous estrogens at female-biased incubation temperatures results in embryos developing as males rather than females. Thus, estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…That is, a slight increase in circulating E 2 resulting from aromatase activity in the brain early in the TSP, coinciding with an increase in ER expression in the gonad, could lead to ovarian differentiation. Bergeron et al (27) measured ER transcripts in the gonads of red-eared slider turtle embryos and found higher concentrations in the gonads of embryos incubated at femaleproducing temperatures at the beginning of the TSP. However, it is not known if the estrogen produced locally in the brain is capable of crossing the blood-brain barrier to an extent great enough to affect circulating steroid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…That is, a slight increase in circulating E 2 resulting from aromatase activity in the brain early in the TSP, coinciding with an increase in ER expression in the gonad, could lead to ovarian differentiation. Bergeron et al (27) measured ER transcripts in the gonads of red-eared slider turtle embryos and found higher concentrations in the gonads of embryos incubated at femaleproducing temperatures at the beginning of the TSP. However, it is not known if the estrogen produced locally in the brain is capable of crossing the blood-brain barrier to an extent great enough to affect circulating steroid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Because primordial follicle formation is associated with significant germ cell attrition (Kezele et al 2002, Pepling 2006, investigations into the associated death mechanisms have been topical and numerous laboratories, using both in vivo and in vitro techniques, have concluded that apoptosis (Coucouvanis et al 1993, De Pol et al 1997, Pepling & Spradling 2001, De Felici et al 2008, Xu et al 2011, autophagy (Lobascio et al 2007, De Felici et al 2008, Rodrigues et al 2009, and direct extrusion from the ovaries (Rodrigues et al 2009) are contributory mechanisms of pre-and neonatal oocyte demise. Apoptosis, the most favored of the three, has been demonstrated not only in mouse models directly targeting Bcl2 and caspase genes (Bergeron et al 1998, Perez et al 1999, Rucker et al 2000, Flaws et al 2001, 2006, Alton & Taketo 2007, Ghafari et al 2007, Greenfeld et al 2007, Gursoy et al 2008 but also because of the findings from several gene knockout (or overexpressor) models belonging to the tumor necrosis factor pathway (Marcinkiewicz et al 2002, Greenfeld et al 2007), PAR family (Wen et al 2009), and TGFb family (Kimura et al 2011), all of which actively participate in oocyte loss by regulating apoptosis.…”
Section: R207mentioning
confidence: 99%
“…Gonadal aromatase (CYP19A1) expression is elevated during and after TSP in alligators and turtles [Smith et al, 1995;Pieau et al, 1999;Gabriel et al, 2001;Murdock and Wibbels, 2003;Pieau and Dorizzi, 2004]. Estrogen receptors (ERs) exist prior to TSP in the genital ridge of the developing red-eared slider turtle and are expressed at a higher density in the future ovary rather than in the testis [Bergeron et al, 1998]. Thus, estrogens are involved in differentiation of an ovary; however, the precise mechanisms and reciprocal actions of estrogens and TSD in reptiles have not been clarified so far.…”
mentioning
confidence: 99%